2005
DOI: 10.1038/sj.leu.2403808
|View full text |Cite
|
Sign up to set email alerts
|

High expression of EDAG and its significance in AML

Abstract: ReferencesThe expression of EDAG mRNA in the leukemia cell lines and other samples were detected by semiquantitative RT-PCR. The PCR conditions and the numbers of cycles were chosen according to preliminary experiments in which the amount of product was directly proportional to the quantity of starting cDNA. In summary, total cellular RNA was extracted with the use of Trizol Reagent (Invitrogen). mRNA from 1 mg of total cellular RNA was reverse transcribed using an M-MLV reverse transcriptase commercial kit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…A recent study has reported an inverse relationship between HEMGN/EDAG expression and the chemotherapy response for AML patients 6 and our own results strongly suggest a causal relationship between GATA1 and EDAG in primary AMLs. Since mutation of GATA1 has been shown to contribute to the chemotherapy sensitivity of AML in Down's syndrome patients, 12 it is conceivable that the downregulation of HEMGN may be involved in molecular mechanisms of the remarkable chemotherapy sensitivity of this unique group of AML patients.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A recent study has reported an inverse relationship between HEMGN/EDAG expression and the chemotherapy response for AML patients 6 and our own results strongly suggest a causal relationship between GATA1 and EDAG in primary AMLs. Since mutation of GATA1 has been shown to contribute to the chemotherapy sensitivity of AML in Down's syndrome patients, 12 it is conceivable that the downregulation of HEMGN may be involved in molecular mechanisms of the remarkable chemotherapy sensitivity of this unique group of AML patients.…”
Section: Discussionmentioning
confidence: 48%
“…6 To further confirm that EDAG is a downstream target of GATA1, we performed the real time RT-PCR to quantify EDAG and GATA1 transcript levels in primary myeloblast specimens. As shown in Figure 6c, both EDAG and GATA1 transcripts varied over a substantial range (for EDAG: 0.06 to 19.85 with a mean of 0.6325; for GATA1: 0.016 to 3.988 with a mean of 0.1350).…”
Section: Increasing the Endogenous Hemgn Transcripts By Gata1 In Cms mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Hemgn in a transgenic mouse model caused an expansion of myeloid hematopoiesis, most particularly in the spleen, 23 and overexpression of the human homolog, EDAG, has been found in acute human leukemia. 24 Based on these findings, we decided to pursue the role of Hemgn in mediating the HOXB4 phenotype.…”
Section: Direct Activation Of Hemgn By Hoxb4mentioning
confidence: 99%
“…EDAG shows similar expression patterns. EDAG expression is high in the BM cells in acute myeloid leukemia, suggesting that EDAG may play a modulator role in acute myeloid leukemia (8). Overexpression of Hemgn in hematopoietic cells suppresses lymphopoiesis and enhances myelopoiesis in transgenic mice, suggesting that Hemgn regulates the proliferation and differentiation of hematopoietic cells (9).…”
mentioning
confidence: 99%